2021
DOI: 10.26434/chemrxiv.13603268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Heavily Substituted Manganite in an Ordered Nanocomposite for Long-Term Energy Applications

Abstract: <div>The implementation of nano-engineered composite oxides opens up the way towards the development of</div><div>a novel class of superior energy materials. Vertically aligned nanocomposites are characterized by a</div><div>coherent, dense array of vertical interfaces, which allows for the extension of local effects to the whole</div><div>volume of the material. Here, we use such a unique architecture to fabricate highly electrochemically</div><div>active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 50 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…28,29,32 In this regard, a previous report investigated the fundamental electrochemical properties of LSM-SDC vertically aligned nanocomposites (VANs) deposited on model single crystal electrolytes. 33 These VANs showed a greatly improved long-term thermal stability with respect to state-of-the-art electrode materials by suppressing the Sr segregation to the surface, along with enhanced oxygen kinetics as a consequence of fast diffusion and incorporation pathways promoted by the microstructural alignment. 33 Moreover, unlike standard multilayer lms, VANs are self-assembled structures, with stable interfaces and chemical compositions formed at growth temperature, that exhibit good microstructural stability during operation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…28,29,32 In this regard, a previous report investigated the fundamental electrochemical properties of LSM-SDC vertically aligned nanocomposites (VANs) deposited on model single crystal electrolytes. 33 These VANs showed a greatly improved long-term thermal stability with respect to state-of-the-art electrode materials by suppressing the Sr segregation to the surface, along with enhanced oxygen kinetics as a consequence of fast diffusion and incorporation pathways promoted by the microstructural alignment. 33 Moreover, unlike standard multilayer lms, VANs are self-assembled structures, with stable interfaces and chemical compositions formed at growth temperature, that exhibit good microstructural stability during operation.…”
Section: Introductionmentioning
confidence: 98%
“…33 These VANs showed a greatly improved long-term thermal stability with respect to state-of-the-art electrode materials by suppressing the Sr segregation to the surface, along with enhanced oxygen kinetics as a consequence of fast diffusion and incorporation pathways promoted by the microstructural alignment. 33 Moreover, unlike standard multilayer lms, VANs are self-assembled structures, with stable interfaces and chemical compositions formed at growth temperature, that exhibit good microstructural stability during operation. In LSM-SDC VANs in particular, spontaneous cationic rearrangement during preparationpossibly caused by the similar cationic radius of La, Sm and Cewas found to promote thermochemical stability by forming a heavily co-doped LSM compound with hindered Sr segregation.…”
Section: Introductionmentioning
confidence: 98%
“…Understanding the oxidation mechanisms of solid materials and analyzing the resultant distribution of oxygen isotopes at nanoscale spatial resolution is pivotal to understanding of a wide variety of processes, including material degradation, [1][2][3][4][5] corrosion of engineered materials, [6][7][8] microorganism corrosion, [9] oxidation of anodes in solid oxide fuel cells, [10] and catalysis. [11,12] In geological sciences mapping 18 O in solid minerals tracer and an environmental reactor chamber attached to the APT system.…”
Section: Introductionmentioning
confidence: 99%
“…[14,17,20,21] Recently, ex situ atom probe tomography (APT) studies validated the ability of APT to achieve sub-nanometerscale spatially resolved mapping of 18 O isotope distribution in materials. [10,[22][23][24][25] However, expanding this ability of APT in mapping 18 O quantitatively at sub-nanometer scale spatial resolution toward in situ oxidation studies is yet to be demonstrated.Here, we demonstrate for the first time in situ APT analysis of oxygen diffusion in a model Fe-18 wt% Cr-14 wt% Ni model alloy (from here on called as Fe18Cr14Ni) using an 18 O isotopic Understanding the early stages of interactions between oxygen and material surfaces-especially at very high spatial resolutions-is highly beneficial for fields ranging from materials degradation, corrosion, geological sciences, forensics, and catalysis. The ability of in situ atom probe tomography (APT) is demonstrated to track the diffusion of oxygen and metal ions at nanoscale spatial resolution during the early stages of oxidation of a model Fe-Cr-Ni alloy.…”
mentioning
confidence: 99%
See 1 more Smart Citation